2006
DOI: 10.1115/1.2728908
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Ratio Effect on Natural Convection Flow in a Cavity Submitted to a Periodical Temperature Boundary

Abstract: The effect of aspect ratio on natural convection flow in a cavity submitted to periodic temperature boundary, is investigated numerically. The temperature of the heated wall is either maintained constant or varied sinusoidally with time while the temperature of the opposite vertical wall is maintained constant. The results are given for a range of varied parameters as Rayleigh number ͑5 ϫ 10 3 ഛ Raഛ 10 6 ͒, cavity aspect ratio ͑1/6ഛ A ഛ 8͒, and period of the sinusoidally heated wall ͑1 ഛ ഛ 1600͒. The amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…In table 2, we have compared our results with those of Ben Cheikh [4]. A Good agreement has been obtained with two results.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…In table 2, we have compared our results with those of Ben Cheikh [4]. A Good agreement has been obtained with two results.…”
supporting
confidence: 68%
“…In our study we found that the time dependent flow begins at around 16 Rac-1, it is the oscillatory mode. The critical value of this mode is Rac2= 4.58×10 4 . In order to view the physical oscillatory flow, we have chosen many arbitrary probes in the cavity.…”
Section: Onset Of Oscillatory Natural Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional verification of accuracy for the present code is shown in Table 2 for the unsteady condition and the case of a differentially heated vertical enclosure with Ra = 1.4 Â 10 5 and Pr = 7. We observe that the comparison was in good agreement with the results reported in the literatures [17,21].…”
Section: Computational Methodologysupporting
confidence: 92%
“…Abourida et al [19] and El Ayachi et al [20] indicated that the heat transfer in a system could be enhanced by a proper choice of the considered parameters. Cheikh et al [21] concluded that the periodical heating case causes an increase of the mean heat transfer in comparison to the constant heating case. Liu et al [22] studied a square conducting body placed at the center of the enclosure.…”
Section: Introductionmentioning
confidence: 99%